Erythroleukemia-historical perspectives and recent advances in diagnosis and management. Issue 2 (March 2018) - Boddu, Prajwal; Benton, Christopher B.; Wang, Wei; Borthakur, Gautam; Khoury, Joseph D.; Pemmaraju, Naveen
Abstract: Acute erythroleukemia is a rare form of acute myeloid leukemia recognized by its distinct phenotypic attribute of erythroblastic proliferation. After a century of its descriptive history, many diagnostic, prognostic, and therapeutic implications relating to this unique leukemia subset remain uncertain. The rarity of the disease and the simultaneous involvement of its associated myeloid compartment have complicated in vitro studies of human erythroleukemia cell lines. Although murine and cell line erythroleukemia models have provided valuable insights into pathophysiology, translation of these concepts into treatment are not forthcoming. Integration of knowledge gained through a careful study of these models with more recent data emerging from molecular characterization will help elucidate key mechanistic pathways and provide a much needed framework that accounts for erythroid lineage-specific attributes. In this article, we discuss the evolving diagnostic concept of erythroleukemia, translational aspects of its pathophysiology, and promising therapeutic targets through an appraisal of the current literature.